Penyusunan Laporan Keuangan yang baik dan benar pada BUMDes - Nur Aliah; Miftha Rizkina; Nina Fadilah (Politeknik Ganesha Medan, 2022)
This research was conducted at BUMDes Mosaik Pematang Serai, Tanjung Pura District, Langkat Regency, North Sumatra. The purpose of this research is to find out how much understanding of village officials in compiling and processing village financial reports so that they can provide further training to improve village officials' skills in preparing village financial reports properly and correctly through community service by providing socialization. This study uses a qualitative descriptive approach by means of interviews. Village-Owned Enterprises or abbreviated BUMDes are formed by the village government to improve the welfare of the village community, utilize all economic potential, economic institutions, as well as the potential of natural resources and village human resources. Most of the business entities in Pematang Serai are engaged in savings and loans, party equipment rental, trading business and management of agricultural and marine businesses. The result of this study is that the knowledge of village officials in preparing financial reports is only limited to recording revenues and expenditures, meanwhile in reporting accountability to the government it must follow established procedures. This research is expected to continue as a community service by providing socialization about village accounting to improve the knowledge and skills of BUMDes managers in Pematang Serai Village, Tanjung Pura District, Langkat Regency, North Sumatra related to knowledge about SOPs for managing BUMDes financial statements.